Perancangan Sistem Antrian Berbasis Web Pada Puskesmas Pangolombian - Krina Crisila T. Mawuntu; Gladly C. Rorimpandey; Kristofel Santa (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study designed and implemented a web-based queuing system at the Pangolombian Health Center. The method applied is the waiting line method with the waterfall system development method. This system uses PHP and MySQL as the programming language and database. Key features include patient registration, scheduling, calling, and real-time queue status display. After implementation, functionality and performance testing is carried out. The results show that this web-based queuing system improves efficiency and patient experience. Patients can register and schedule queues online, reducing waiting times. Automatic queue calling makes it easier for puskesmas staff. Staff and schedule management features help manage queues more efficiently. This research produces an efficient and convenient web-based queuing system. This system has the potential to provide a better experience for patients by reducing waiting times and long queues. This system also assists puskesmas staff in managing queues efficiently. The results of this study can contribute to developing a web-based queuing system at puskesmas and other health institutions